Blanca Luz Brum, poeta y revolucionaria. Sus textos en Amauta (1926-1929) - Rico Alonso, Sonia (2023)
The Uruguayan writer Blanca Luz Brum was an active part of the cultural and socio-political life of different Latin American cities for several decades. However, her ideological estrangement from socialism, as well as her intense love life, earned her disqualification and oblivion. The aim of this paper is to rescue her figure through the analysis of her texts published in the magazine Amauta between 1926 and 1929, taking into account the author’s poetics and the role that her poems occupy in the magazine. The study will reveal the double aspect of her poetry: one that is political, gimmicky and has a propagandistic and mobilizing character; and the personal one, which is more complex, deep and reflects the most intimate side of Blanca Luz.